Simultaneous laparoscopic and thoracoscopic intervention for lung metastases from rectal cancer (a clinical case) - M. I. Davydov; M. M. Davydov; A. O. Rasulov; A. K. Allakhverdiev; D. V. Kuz’michev; A. V. Polynovskiy; Yu. E. Suraeva (Тазовая хирургия и онкология, 2016)
The paper describes a clinical case of successful treatment in a female patient with disseminated rectal cancer by minimally invasive technologies that could perform one-stage simultaneous intervention into the rectum and lung, which promoted rapid patient rehabilitation and reduced systemic chemotherapy initiation time.